Tinjauan Tentang Metode Pengupahan Terhadap Karyawan Di UD. Melinda Bakery Surakarta - Setiawan, Andi; , Darsono, S.H., M.H; , Nuswardhani, S.H., M.H (2015)
The purpose of this study was to determine: 1) how to wage UD Melinda Bakery Surakarta relation to the regulation of wages; 2) the influence of the wages of workers on the way Melinda Bakery UD held in Surakarta. This research includes normative legal research is to identify and mengkonsepsi law as the norm rules, regulations, laws in force at a particular time and place. Research conducted at UD Melinda Bakery Surakarta. Source of data using secondary data from the literature studies, interviews, and observations. Data were analyzed using qualitative analysis. The results showed that: 1) How to use the wage bill Melinda Trade Enterprises (UD) Bakery is based on calculations by the company and are based on the financial state of the company, consisting of: base salary, meal / tranport, overtime pay, incentive, health benefits, and holiday allowance (THR). The amount of the daily wage for employees is Rp. 40.000, - and monthly employee is Rp. 1.250.000, -. The amount of the monthly wage for employees is in conformity with the provisions of the regional minimum wage (UMR) established by the Governor of Central Java on the minimum wage in the city of Surakarta in 2013 was Rp 1.145.000, -; 2) Wages given by UD Melinda Bakery has been good. Wages Employees can take part in wage policy through through union / labor unions.